Being-Towards-Death in The Digital Age (Existential Analysis: Journal of the Society for Existential Analysis, 2012)
The enduring and growing popularity of social networking sites and technologically mediated communications means that not only are we increasingly telepresent with one another in life, but we leave behind a digital legacy when we die, often to include detailed, co-constructed representations of ourselves in the form of, for example, Facebook profiles. Life in the digital age has interesting implications when viewed in the context of existential givens such as Being-in-the-body, Being-with-others-in-the-world, and Being-towards-death, and in this paper these implications will be discussed, particularly with reference to Heidegger.
Keywords: Being-towards-death; Heidegger; Facebook; social networking; technologically mediated mourning; bereavement